Penerapan Model PBL pada Pembelajaran Bahasa Indonesia Materi Teks Prosedur Kelas V untuk Meningkatkan Keaktifan Siswa - Hamida, Khoirul; Saputra, Henry Januar; Handayani, Retno Suci (WASIS : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this research is to analyze Indonesian language learning for class V procedural text material using  Problem Basic Learning (PBL) to increase student activity.The research method used was Classroom Action Research (PTK).The research was carried out in two cycles where each cycle consisted of planning, implementing actions, observing and reflecting. The research was conducted on class V students at SD Negeri Bendungan Semarang, totaling 26 students. In this research, data analysis uses qualitative data and quantitative data which is analyzed using descriptive techniques.The results of the research showed that there was an increase in the average results of students' classical learning activities carried out from pre-cycle actions to cycle I and cycle II. The average percentage of student learning activities in the pre-cycle was 49.15% in the "low" category. In cycle I, the average percentage of student learning activity increased by 72.42% with the student activity category being "medium". Meanwhile, in cycle II the average percentage of student learning activity increased by 87.73% with the student activity category being "high". So, the results of observations and questionnaire sheets on student learning activities in Indonesian language learning using the Problem Basic Learning (PBL) learning model can increase the learning activities of class V students in Indonesian Procedure Text material at SD Negeri Bendungan Semarang in 2023/2024 school year.